(untitled) (Revista Apotheke, 2022)
This paper addresses the connection between education and life, through one situation of the teaching and learning of art created in the interwoven of the two fictions: “Having an experience” by John Dewey and “Where is the friend’s home?” by Abbas Kiarostami.